Massively Multiuser Virtual Environments using Object Based Sharing - Sonnenfroh, Michael; Möller, Kim-Thomas; Müller, Marc-Florian; Schoettner, Michael; Schulthess, Peter (Electronic Communications of the EASST, 2009)
Massively multiuser virtual environments (MMVEs) are becoming increasingly popular with millions of users. Commercial implementations typically rely on a traditional client/server architecture controlling the virtual world state of shared data at a central point. Message passing mechanisms are used to communicate state changes to the clients. For scalability reasons our approach creates and deploys MMVEs in a peer-to-peer (P2P) fashion. We use standard Java technology implementing only a few basic data-centric operations for the management of our distributed objects. Higher consistency models can easily be implemented using these basic operations. Currently, we have implemented transactional consistency offering convenient and consistent access to the shared scene graph. In this paper we describe our basic object model and the prototype implementation TGOS (Typed Grid Object Sharing). Furthermore, we discuss preliminary measurements with the virtual world Wissenheim executed on top of TGOS.